Cationic Complexes of Boron and Aluminum: An Early 21st Century Viewpoint. Issue 12 (10th December 2018) - Franz, Daniel; Inoue, Shigeyoshi
Abstract: Boron and aluminum are lighter Group 13 elements, found in daily life commodities, and considered environmentally benign. Nevertheless, they markedly differ in their elemental properties (e.g., metal character, atomic radius). The use of Lewis acidic complexes of boron and aluminum for methods of bond activation and catalysis (e.g., hydrogenation of unsaturated substrates, polymerization of olefins and epoxides) is quickly expanding. The introduction of cationic charge may boost the metalloid‐centered Lewis acidity and allow for its fine‐tuning particularly with regard to preference for "hard" or "soft" Lewis bases (i.e., substrates). Especially the isolation of low‐coordinate cations (number of ligand atoms smaller than four) demands elaborate techniques of thermodynamic and kinetic stabilization (i.e., electronic saturation and steric shielding) by a ligand system. Furthermore, the properties of the solvent and the counteranion must be considered with care. Here, selected examples of boron and aluminum cations are described. Abstract : Be positive ! The coordination chemistry of boron and aluminum cations has been attracting attention due to the use of these compounds as main‐group catalysts. Sophisticated ligand systems have been employed and fine‐tuning of the Lewis acidity of low‐coordinate complexes has been accomplished by introduction of one or more cationic charges. By this, the selectivity for "hard" or "soft" Lewis bases/substrates can be modified.